2020
DOI: 10.3390/su12072746
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Different Air Pollutants on Dining-Out Activities and Satisfaction of Urban and Suburban Residents

Abstract: Air pollution has become a global environmental problem that directly affects the living quality of city residents. It not only does damages to the physical health of the human body but also has adverse effects on mood, outdoor activities, and social interactions, which further reduces the vitality of the city. Dining out is an important way of social interaction for city residents. Using Beijing as an example, this paper aims to study the impacts of different air pollutants on dining-out activities and satisf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 48 publications
(46 reference statements)
0
4
0
Order By: Relevance
“…The number is much higher than the study of Zheng, this may be because they combine types of eating out for breakfast, lunch and dinner, while our study only considers lunchtime and dinner. Further, another similar study, Gao et al [ 24 ] concludes that for every 1% increase in the concentrations of PM 2.5 , the dining-out frequency of urban residents reduces 0.059% around Beijing in 2016. In our case, if PM 2.5 increases by 1% (0.97 μg/m 3 ), the density of actual people in the restaurant VP would decrease by person/km 2 , equal to a decrease in 0.44% for people eating out for lunch.…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…The number is much higher than the study of Zheng, this may be because they combine types of eating out for breakfast, lunch and dinner, while our study only considers lunchtime and dinner. Further, another similar study, Gao et al [ 24 ] concludes that for every 1% increase in the concentrations of PM 2.5 , the dining-out frequency of urban residents reduces 0.059% around Beijing in 2016. In our case, if PM 2.5 increases by 1% (0.97 μg/m 3 ), the density of actual people in the restaurant VP would decrease by person/km 2 , equal to a decrease in 0.44% for people eating out for lunch.…”
Section: Resultsmentioning
confidence: 91%
“…Thus, FEMs can be applied to detect the relationship between ADLs and air pollution where the model is an estimation technique, employed on panel data that allows one to account for time-invariant unobserved individual characteristics, i.e., other factors such as special offers at different times of day, etc., that can be correlated with the observed independent variables (AQI or PM 2.5 ) [ 23 ]. For example, Gao et al [ 24 ] studied the impact of different air pollutants on dining-out activities and the satisfaction of urban and suburban residents. They found that due to differences in environmental and health awareness, the impact of air pollution on dining-out behaviours varies among urban and suburban residents.…”
Section: Related Workmentioning
confidence: 99%
“…For example, people who are exposed to a high level of SO 2 (e.g., miners) are more likely to suffer from irritability, sleeping disorders, and a loss of appetite (Hilson, 2003). Gao and colleagues (2020) conclude that O 3 pollution has a negative emotional impact on people. More specifically, O 3 certainly reduces dining-out satisfaction (Gao et al, 2020).…”
Section: Literature Reviewmentioning
confidence: 89%
“…Gao and colleagues (2020) conclude that O 3 pollution has a negative emotional impact on people. More specifically, O 3 certainly reduces dining-out satisfaction (Gao et al, 2020). As these pollutants influence different areas, such as personal emotions, health, and appetite (Ferreira et al, 2013;Klatzkin et al, 2019), a possible downstream consequence is food consumption behavior, which has been under-researched.…”
Section: Weather and Food Wastementioning
confidence: 99%